Innovative methods in technological education. (Paris : UNESCO, 1989)
In many countries today the education of technologists is continuing to undergo intensive scrutiny and reappraisal by teachers and industrialist. This is particularly true of engineers, for they are mostly concerned with the design and production of capital goods, expendable goods and consumer goods, and with the operation of complex systems.
1. Engineering education and its problem -- 2. A glance at the papers in part two -- 3. Teaching non-technical matters and attitudes -- 4. New impacts of computers in education -- 5. Laboratory work and projects -- 6. Educational software in developing countries -- 7. Distance education -- 8.Engineering education at new types of university -- 9. Continuing education.
Includes bibliographical references.
Keywords: ENGINEERING STUDY AND TEACHING